HUBUNGAN ANTARA STRES KERJA DAN MOTIVASI BERPRESTASI DENGAN KINERJA GURU - Dapid Candra; Rambat Nur Sasongko; Zakaria Zakaria (Manajer Pendididikan, 2017)
The purpose of this  research was to describe the correlation between work stress and achieved motivation with teacher’s perfomance at the junior high school teachers at Manna East of Bengkulu. The method of research was correlational. The data was collected by using questionnaire, the data analysis was correlation, linear regression, and double regression to examine the hypotesis. The results of this research were (1) There was significant relation between work stress and teachers perfomance; (2) There was significant relation between achieved motivation and teachers perfomance; (3) There was together relation between work stress and achieved motivation to the teachers perfomance. According to the first and the second hyphothesis, it was conversed to the third hyphotesis, it was estimated that work stress followed by achieved motivation will increase the teachers perfomance.